Staying out of range: Increasing attacking distance in fencing - Turner, A. N.; Marshall, G.; Noto, A.; Chavda,S.; Atlay, N.; Kirby, D. (International Journal of Sports Physiology and Performance, 2017)
To avoid being hit, fencers typically adopt an out-of-range position, which was hypothesized to be governed by body- and action-scaled affordances. This theory was measured in elite and national-level junior (under 20 y of age) fencers. Associations between "reachability" of lunging and step-lunging attacks were assessed against height, arm span, leg span, body mass, and lower-body power and then compared across level. Reachability was determined as the distance covered by fencers during these attacks and was reported as actual and estimated distances. Elite fencers are better at estimating their lunging and step-lunge distance compared to nationally ranked junior fencers (-0.9% vs 7.3% and 5.4% vs 10.9%, respectively). Surprisingly, elite fencers` actual and estimated distances for these was less than the junior fencers` (222.6 vs 251.5 cm and 299.3 vs 360.2 cm, respectively), and significantly so in the former. Finally, only arm span (r=.81) and leg span (r=.71) were significantly correlated to estimated lunging distance, and this was only in elite fencers. Findings suggest that better fencers can accurately predict their attack range and that reachability appears to be positively influenced by arm and leg span; these may feed in to talent identification. Given that distances were less in elite fencers, findings suggest that timing and distance estimation are key skills to master and that the mastery of these in offensive actions can mitigate, to a large extent, the physical benefits of an opponent`s greater height.